Total Alkaloids of Rhizoma Corydalis regulates gut microbiota and restores gut immune barrier to ameliorate cognitive dysfunction in diabetic rats - Qi, Yazhi; Li, Jun; Tang, Ya; Cao, Rui; Gao, Yishu; Xu, Qiang; Han, Yusheng (Frontiers in Microbiology, 2024)
Background and objectivesGiven the widespread dysbiosis of gut microbiota in patients with T2DM, it has been found that the microbiota-gut-brain axis plays an influential regulatory role in diabetic cognitive dysfunction, and improving gut dysbiosis may be a potential strategy for treating diabetic cognitive dysfunction. Total Alkaloids of Rhizoma Corydalis (TAC) is the main active component extracted from Rhizoma Corydalis. Pharmacological studies have demonstrated its significant pharmacological effects on the cardiovascular and cerebrovascular systems, and berberine, the main component of TAC, has a certain regulatory effect on gut microbiota.Materials and methodsRats were randomly divided into Control group, Model group, TAC-low group, TAC-mid group and TAC-high group. Cognitive function of diabetic rats was evaluated through behavioral testing using the Morris water maze experiment. The relative abundance of gut bacteria in rat feces was determined via 16S rRNA analysis. IHC and Western blot techniques were employed to assess IL-22, IL-23, Reg3g, ZO-1, occludin 1 expression in the colon tissue; GPX4, xCT, NLRP3, Caspase-1 p20, GSDMD-N were detected in the hippocampus.ResultsThe cognitive function of diabetic rats decreased significantly. TAC demonstrated a significant reduction in inflammatory factors in serum, hippocampus, and colon, thus alleviating inflammation. Additionally, it effectively decreased ferroptosis induced by NLRP3 and reduced pathological damage in the hippocampus of diabetic rats. After treatment, the differential microbiota such as Lachnoclotridium and Bacteroides. TAC improved gut barrier permeability and integrity in rats while remodeling gut mucosal homeostasis. Moreover, pyroptosis and ferroptosis caused by the inflammatory cascade in the rat hippocampus were also significantly inhibited.ConclusionThe combination of high lipid and high glucose with STZ can result in gut microbiota disturbance, damage gut immune barrier, decreased gut mucosal permeability and integrity, aggravated gut inflammation, further spread inflammatory factors to brain tissue, cause inflammatory cascade reaction of encephalopathy, and ultimately resulting in neuronal ferroptosis and cognitive dysfunction in diabetes mellitus. Our study suggests that TAC may regulate gut microbiota, restore gut immune homeostasis, improve gut barrier permeability and integrity, inhibit brain tissue inflammatory cascade, reduce neuronal ferroptosis, and thus improve diabetes. This provides new targets for its treatment strategy.